Modeling and simulation of launch vehicles using object-oriented programming - Fábio Antônio da Silva Mota (2015)
Due to the inherent complexity of a launch vehicle, its design is traditionally divided into multiple disciplines, such as trajectory optimization, propulsion, aerodynamics and mass budget. Despite the large number of operational launch vehicles, they usually consist of basic components. In other words, a launch vehicle is an assembly of stages which in turn is divided into propellant system and engine (for a liquid rocket stage), and the engine is an assembly of basic components such as pumps, turbines, combustion chamber, and nozzle. Then, in order to allow future extension and reuse of the codes, it is reasonable that a modular approach would be a suitable choice. In this work, this is accomplished by object-oriented methodology. The UML (Unified Modeling Language) tool was used to model the architecture of the codes. UML diagrams help to visualize the structure of the codes and communication between objects enabling a high degree of abstraction. The purpose of this thesis is the development of a versatile and easily extensible tool capable of analyzing multiple configurations of liquid rocket engines and calculating the performance of satellite launch vehicles. The verification of the codes will be performed by the simulation of power cycle of liquid rocket engines and by the trajectory optimization of the launch vehicles VLS-1 and Ariane 5. In order to verify the applicability of the tool concerning communication between propulsion system and launcher performance, the VLS-Alfa will be simulated for a given mission for diferent design parameters of the rocket engine upper stage.